2003
DOI: 10.1002/mats.200350007
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Weight and Long Chain Branch Distributions of Branch‐Block Olefinic Thermoplastic Elastomers

Abstract: Olefinic thermoplastic elastomers can be prepared by incorporating semi‐crystalline macromonomers (e.g. isotactic or syndiotactic poly(propylene), high‐density polyethylene) onto amorphous backbones (e.g. atactic poly(propylene), ethylene/α‐olefin copolymers). The macromonomer incorporation reaction can be carried out in semi‐batch reactors by adding previously synthesized macromonomers to the reactor (ex situ approach), or by generating and incorporating the macromonomers in a single step (in situ approach). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 20 publications
0
16
1
Order By: Relevance
“…The melting temperature, the cold crystallization temperature, the glass transition temperature, as well as the crystallinity from the heat of fusion are tabulated in Table 1. In contrast to the other reported miscible crystalline-amorphous polymer blends, [12][13][14][15][16][17][18][19] no apparent melting temperature depression and crystallinity decrease are observed for PVDF upon increasing ACM content. However, it is found that PVDF crystallization Thermoplastic Acrylic Rubber Physically Crosslinked by Tiny Poly(vinylidene fluoride) Crystals temperature from the melt decreases greatly with increasing ACM content, indicating that the PVDF crystallization speed is reduced by addition of ACM.…”
Section: Pvdf Micro-crystals In Acm/pvdf Blendscontrasting
confidence: 42%
See 1 more Smart Citation
“…The melting temperature, the cold crystallization temperature, the glass transition temperature, as well as the crystallinity from the heat of fusion are tabulated in Table 1. In contrast to the other reported miscible crystalline-amorphous polymer blends, [12][13][14][15][16][17][18][19] no apparent melting temperature depression and crystallinity decrease are observed for PVDF upon increasing ACM content. However, it is found that PVDF crystallization Thermoplastic Acrylic Rubber Physically Crosslinked by Tiny Poly(vinylidene fluoride) Crystals temperature from the melt decreases greatly with increasing ACM content, indicating that the PVDF crystallization speed is reduced by addition of ACM.…”
Section: Pvdf Micro-crystals In Acm/pvdf Blendscontrasting
confidence: 42%
“…[11] Recently, some authors reported a new method to prepare TPEs by modifying amorphous polymers with semicrystalline branches, where the hard crystalline domains from the branch act as physical crosslinks tying the amorphous segments in a three-dimensional networks. [12,13] On the other hand, Vara et al [14] have prepared a high-hardness ethylene-propylene-diene terpolymer (EPDM) TPE by blending a semi-crystalline EPDM with an amorphous EPDM.…”
Section: Introductionmentioning
confidence: 99%
“…[42] Population balance models for TPE production were developed to help explain the differences between polymers made with the sequential or simultaneous modes of operation. [42,43] The simulations show that the sequential procedure is always more effective in making highly branched polymers for the same polymerization conditions. This is mainly because, in the simultaneous mode of operation, no macromonomers are present at the beginning of the polymerization and therefore LCB formation will only take place after a certain time interval has elapsed.…”
Section: Heterogeneous Branching With Dual Catalystsmentioning
confidence: 99%
“…Simultaneous (a) versus sequential (b) TPE production. [43] Figure 19. Chain length distribution TPE chains with one (a) and two LCBs (b).…”
Section: Heterogeneous Branching With Dual Catalystsmentioning
confidence: 99%
“…Obtained results are in accordance with simulations and experimental studies performed for similar systems. [22,23] Based on the discussions presented in the previous paragraphs, it can be concluded that obtained numerical solutions were stable and meaningful in all cases, indicating the appropriateness of the proposed numerical implementation. Besides, it was shown in all analyzed cases that ten collocation points were sufficient to guarantee the convergence of the proposed numerical scheme; for this reason, unless stated otherwise, ten collocation points were used in all simulations performed in the following sections.…”
Section: Simulation Studiesmentioning
confidence: 75%